(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2018)
This paper discusses the research that has been done in the field of Human Computer Interaction (HCI) relating to human psychology. A brief overview of HCI is presented. Specific examples of research in the areas of icons and menus are then reviewed. The results of these experiments and the predictions they make about general human psychology and specific human interaction with computers is discussed. Mental models of user interface interaction are discussed and compared to mental models of real world object. Finally, future directions for research are proposed. The past decade has witnessed an unprecedented growth in user interface and human–computer interaction (HCI) technologies and methods. The synergy of technological and methodological progress on the one hand, and changing user expectations on the other, are contributing to a redefinition of the requirements for effective and desirable human–computer interaction. A key component of these emerging requirements and of effective HCI in general, is the ability of these emerging systems to address user affect. The objective of this special issue is to provide an introduction to the emerging research area of affective HCI, some of the available methods and techniques, and representative systems and applications. “The question persists and indeed grows whether the computer will make it easier or harder for human beings to know who they really are, to identify their real problems, to respond more fully to beauty, to place adequate value on life, and to make their world safer than it now is”.